Safety and Efficacy of Cell Transplantation on Improving Motor Symptoms in Patients With Parkinson’s Disease: A Meta-Analysis - Wang, Jiaming; Tian, Yu; Shi, Xin; Feng, Zhaohai; Jiang, Lei; Hao, Yujun (Frontiers in Human Neuroscience, 2022)
Background: The past four decades have seen the growing use of tissue or cell transplants in Parkinson's disease (PD) treatment. Parkinson's cell therapy is a promising new treatment; however, efficacy of cell transplantation for Parkinson's disease are entirely unclear. Objective: To conduct a meta-analysis and a systematic review of the efficacy of cell therapy in patients with PD. Methods: A systematic literature review and meta-analysis of 10 studies were performed to assess the efficacy of cell therapy in Parkinson's patients. To achieve this, we compared the change in Unified Parkinson's Disease Rating Scale (UPDRS) II & III scale scores to baseline and assessed the incidence of transplant-related adverse events. The MINORS score and the I2 index were applied to evaluate the quality of studies between-study heterogeneity, respectively. Results: The literature search yielded 10 articles (n=120). The improvement in motor function based on the UPDRSIII assessment was -14.044 (95% CI: -20.761, -7.327) (p < 0.001), whereas improvement in daily living ability based on the UPDRSII assessment was -5.661 (95% CI: -7.632, -3.689) (p < 0.001). Conclusions: The present findings demonstrate important clues on the therapeutic effect of cell therapy in alleviating motor impairment and daily living ability in PD patients.